Plasma Soluble Dipeptidyl Peptidase-4 and Risk of Major Cardiovascular Events After Ischemic Stroke: Secondary Analysis of China Antihypertensive Trial in Acute Ischemic Stroke (CATIS). (30th August 2022) - You, Shoujiang; Miao, Mengyuan; Lu, Zian; Bao, Anran; Du, Jigang; Che, Bizhong; Xu, Tan; Zhong, Chongke; Cao, Yongjun; Liu, Chun-Feng; Zhang, Yonghong; He, Jiang
Abstract : Background and Objectives: Recent studies have suggested that plasma soluble dipeptidyl peptidase-4 (sDPP4) have important physiologic effects, which may influence the prognosis of ischemic stroke. Our study aimed to examine the relationship between plasma sDDP4 levels and long-term clinical outcomes among patients with acute ischemic stroke. Methods: Secondary analysis was conducted among 3, 564 participants (2, 270 men and 1, 294 women) from the China Antihypertensive Trial in Acute Ischemic Stroke with baseline measurement of plasma sDPP4 levels. We evaluated the associations between plasma sDPP4 levels and 2-year clinical outcomes using logistic regression and Cox regression models. We further investigated the predictive utility of sDPP4 by calculating net reclassification index and integrated discrimination improvement. Results: The highest plasma sDPP4 quartile was associated with lower risk of cardiovascular events (hazard ratio [HR] 0.62, 95% confidence interval [CI] 0.45–0.87), recurrent stroke (HR 0.70, 95% CI 0.49–0.99), all-cause mortality (HR 0.62, 95% CI 0.44–0.87), stroke-specific mortality (HR 0.65, 95% CI 0.44–0.94), and poor functional outcomes (odds ratio 0.66, 95% CI 0.53–0.82) at 2 years compared with the lowest sDPP4 category in multivariable models. The addition of plasma sDPP4 to conventional risk factors model significantly improved risk prediction of all outcomes. Discussion: In this study, we found that higher plasma sDPP4 levels in patients with acute ischemic stroke were associated with decreased risks of cardiovascular events, recurrent stroke, all-cause mortality, and poor functional outcomes after ischemic stroke. These findings suggest that plasma sDPP4 may be a potential prognostic marker for initial risk stratification in patients with acute ischemic stroke.